24 chiclayanas couples treatment by artificial insemination homologous with the first fraction of the ejaculate. - Palacios Celi, Miguel (2015)
-IAH- Homologous artificial insemination is a method that progressively becomes more important in the treatment of conjugal sterility and involves depositing fresh semen, frozen or treated in the ectocervix, endocervix or the endometrial cavity, in this paper we have used sperm fresh fractionated using the first fraction of the ejaculate and have placed in the endocervix with spray peri-cervical, compared with classical insemination around the ejaculate. The sample of 24 partners, we divided into two groups of 12 couples c / u., Group A was seeded with the first portion of the ejaculate, while group B was inseminated with all the ejaculated, all couples received the same protocol of ovarian induction, ultrasound screening procedure of ovulation and insemination; the results were tabulated, analyzed and distributed in two-dimensional pictures.